Mutation of a Salmonella serogroup-C1-specific gene abrogates O7-antigen biosynthesis and triggers NaCl-dependent motility deficiency. - Xiujuan Zhou (Public Library of Science (PLoS), 2014)
Several molecular detection marker genes specific for a number of individual Salmonella serogroups have been recently identified in our lab by comparative genomics for the genotyping of diverse serogroups. To further understand the correlation between serotype and genotype, the function of a Salmonella serogroup-C1-specific gene (SC_2092) was analyzed in this study. It was indicated from the topological prediction using the deduced amino acid sequence of SC_2092 that this putative protein was highly similar to the confirmed Wzx flippases. Furthermore, SDS-PAGE revealed that lipopolysaccharide (LPS) biosynthesis, specifically O-antigen synthesis, was incomplete in an SC_2092 in-frame deletion mutant, and no agglutination reaction with the O7 antibody was exhibited in this mutant. Therefore, it was revealed that this Salmonella serogroup-C1-specific gene SC_2092 encoded a putative flippase, which was required for O7-polysaccharide biosynthesis, and was designated here as wzxC1. Subsequently, the effects of the deletion of wzxC1 on bacterial motility and sodium chloride (NaCl) tolerance were evaluated. The wzxC1 mutant lacked swarming motility on solid surfaces and was impaired in swimming motility in soft agar. Moreover, microscopic examination and RT-qPCR exhibited that an increased auto-aggregation and a strong defect in flagella expression, respectively, were responsible for the reduced motility in this mutant. In addition, the wzxC1 mutant was more sensitive than the wild-type strain to NaCl, and auto-aggregation of mutant cells was observed immediately up on the addition of 1% NaCl to the medium. Interestingly, the motility deficiency of the mutant strain, as well as the cell agglomeration and the decrease in flagellar expression, were relieved in a NaCl-free medium. This is the first study to experimentally demonstrate a connection between a Salmonella serogroup specific gene identified by comparative genomics with the synthesis of a specific O-antigen biosynthesis. Also, our results show that the mutation of wzxC1 triggers a NaCl-dependent motility deficiency.